PERAN KETELADANAN GURU AGAMA KRISTEN DALAM PEMBENTUKAN SPIRITUALITAS SISWA KRISTEN DI SD NEGERI REJOSARI SURAKARTA - Bangun, Vanny Yolanda Br.; Juntak, Justin Niaga Siman (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
This study aims to analyze the role of Christian Religious Education (PAK) teachers’ exemplary character in shaping the spirituality of Christian students at SD Negeri Rejosari Surakarta. The research is motivated by the rise of negative behaviors such as bullying and the weak internalization of spiritual values among students, highlighting the need for teacher exemplarity as a key instrument of faith education. Using a qualitative approach through interviews, observations, and document analysis, this study explores insights from teachers, students, and the principal. The findings reveal that the exemplary life of PAK teachers significantly influences students’ spiritual formation, moral development, and social behavior. Teachers function as spiritual and moral models whose consistent demonstration of love, patience, honesty, and humility is observed, imitated, and internalized by students. Warm teacher–student relationships create a safe spiritual space, while exemplary actions within learning activities make faith values more concrete and meaningful. Teacher exemplarity also contributes to a positive school culture, fostering polite interactions, peaceful conflict resolution, and a harmonious classroom atmosphere. Despite challenges such as religious diversity and the characteristics of digital-era children, institutional support and moral recognition strengthen the teacher’s role. Overall, the study concludes that the exemplarity of PAK teachers serves as the primary foundation of students’ spiritual development and represents the core of Christian pedagogy that integrates faith and daily practice. ABSTRAK Penelitian ini bertujuan untuk menganalisis peran keteladanan guru Pendidikan Agama Kristen (PAK) dalam pembentukan spiritualitas siswa Kristen di SD Negeri Rejosari Surakarta. Latar belakang penelitian berangkat dari meningkatnya perilaku negatif seperti bullying serta lemahnya internalisasi nilai spiritual pada siswa, sehingga keteladanan guru menjadi instrumen penting dalam pendidikan iman. Penelitian ini menggunakan pendekatan kualitatif dengan teknik wawancara, observasi, dan analisis dokumen untuk menggali pengalaman guru, siswa, dan kepala sekolah. Hasil penelitian menunjukkan bahwa keteladanan guru PAK memiliki pengaruh signifikan dalam pembentukan iman, karakter, dan perilaku sosial siswa. Guru menjadi model spiritual dan moral yang diamati, ditiru, dan diinternalisasi siswa melalui konsistensi hidup yang mencerminkan kasih, kesabaran, kejujuran, dan kerendahan hati. Relasi guru–siswa yang hangat menciptakan ruang spiritual yang aman, sedangkan keteladanan dalam proses pembelajaran menjadikan nilai iman lebih bermakna. Pengaruh keteladanan juga tampak pada budaya sekolah melalui munculnya interaksi yang sopan, penyelesaian konflik secara damai, serta atmosfer kelas yang harmonis. Penelitian ini juga menemukan tantangan seperti keberagaman agama dan karakter siswa era digital, tetapi dukungan kepala sekolah, fasilitas, dan pengakuan moral memperkuat peran guru. Secara keseluruhan, keteladanan guru PAK terbukti sebagai fondasi utama pembentukan spiritualitas siswa dan merupakan inti pedagogi Kristen yang mengintegrasikan iman dan tindakan.